Enhancement of the antibiotic activity mediated by the essential oil of Ocotea odorifera (VELL) ROWHER and safrole association. Issue 3 (March 2022) - de Almeida, Ray Silva; Ribeiro-Filho, Jaime; Freitas, Priscilla Ramos; de Araújo, Ana Carolina Justino; dos Santos, Eduardo Lourenço; Tintino, Saulo Relison; Moura, Talysson Felismino; Ferreira, Vitória Assunção; Ferreira, Beatriz Assunção; Juno Alencar Fonseca, Victor; Leite, Pedro Ivo Palacio; Albuquerque da Silva, Ana Cristina; et al.
Abstract: In a recent study, our research group demonstrated that the essential oil of Ocotea odorifera (EOOO) and its major compound safrole potentiated the action fluoroquinolones, modulating bacterial resistance possibly due to direct inhibition of efflux pumps. Thus, in the present study, we investigated whether these treatments could enhance the activity of gentamicin and erythromycin against multidrug-resistant (MDR) bacteria. The EOOO was extracted by hydrodistillation, and the phytochemical analysis was performed by gas chromatography coupled to mass spectrometry (GC–MS). The antibiotic-enhancing effect of the EOOO and safrole against MDR strains of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa was analyzed by the broth microdilution method. The chemical analysis confirmed the presence of safrole as a major component among the 16 compounds identified in the EOOO. Both the essential oil and the isolated compound showed clinically relevant antibacterial activities against S. aureus . Regarding the modulation of antibiotic resistance, the EOOO was found to enhance the activity of erythromycin against the strains of P. aeruginosa and S. aureus, as well as improving the action of gentamicin against S. aureus . On the other hand, safrole potentiated the activity of gentamicin against the S. aureus strain alone. It is concluded, therefore, that the EOOO and safrole can enhance the activity of macrolides and aminoglycosides, and as such are useful in the development of therapeutic tools to combat bacterial resistance against these classes of antibiotics.